The Branding Efforts of Snapdeal and the Quest for Profits : A Case Study - Rajan, Thomason; Alexander, Jacob (Indian Journal of Marketing, 2019)
Snapdeal, the Indian online retail firm, started its journey as a discount coupon service and moved on to the marketplace model after the founders Kunal Bahl and Rohit Bansal made a trip to China. With steady growth in business, the company started focusing on branding and positioned itself on the wide product assortment platform. Using several campaigns and roping in brand ambassadors, including Bollywood actor Aamir Khan, the brand achieved its targets of registered customers, sellers, and delivery points. The company struggled to make profits and to add to the trouble, there was a controversy over a statement made by Aamir Khan. The founders devised a leaner, asset-light model called Snapdeal 2.0 and focused on multiple sources of revenue. Eventually, their efforts paid off and after 11 years, the company started making profits. The case discussed the steps taken by the founders to build the brand and turn it profitable. The nuances stated in the case will help students in marketing to understand the need to balance campaign spends with brand profits and also make them appreciate the multiple challenges that entrepreneurs face while building brands.